(untitled) (Mustansiria Dental Journal, 2004)
A 102 (68 males and 34 females) dental student and staff questioned whether or not having experienced aphthus ulceration (Au). A questioner form which shows later ni the text, was prepared. Data showed females experienced (Au) more than males and individual with blood group AB have higher liability than individuals with other blood groups. The inner site of the lip was the com monest site affected. Majority of individuals with (Au) were able to relate their condition to variable stress and emotional factors. Individuals with smoking habit are very rarely affected by Au.